2013
DOI: 10.5603/ep.2013.0005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum prohepcidin and iron metabolism parameters in obese and non-obese elderly individuals

Abstract: Introduction: Current knowledge indicates that there is a close connection between being overweight, obesity and iron metabolism disorders, but the underlying mechanism is unclear. Hepcidin could be a major contributor to poor iron status observed in the obese population. Material and methods:The study was performed in 58 obese elderly individuals (F/M 34/24) aged 65-91 (78.92 ± 8.32) years. The control group consisted of 15 non-obese elderly volunteers, age-and sex-matched. Based on the WHO definition, 36 (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Alterations in hepcidin levels have been reported in chronic diseases with iron deposition [4, 5]. There are a growing number of studies targeting the possible role of hepcidin in the pathogenesis of insulin resistance and related diseases [68]. Decreased or unchanged hepcidin concentrations have been found in patients with polycystic ovary and metabolic syndrome [911].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in hepcidin levels have been reported in chronic diseases with iron deposition [4, 5]. There are a growing number of studies targeting the possible role of hepcidin in the pathogenesis of insulin resistance and related diseases [68]. Decreased or unchanged hepcidin concentrations have been found in patients with polycystic ovary and metabolic syndrome [911].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation may perpetuate this condition through the hepcidin-mediated inhibition of iron absorption 7 . A preliminary study suggested that body fat affects prohepcidin concentration and thereby affects iron haemostasis 34 . In childhood, obesity increases hepcidin levels and is associated with a diminished response to oral iron therapy in cases of iron deficiency anaemia 35 …”
Section: Discussionmentioning
confidence: 99%
“…In obese subjects hepcidin concentration, produced by adipocytes, is significantly increased. It inhibits the intestinal absorption of iron and its release from macrophages and liver, leading to its accumulation in the body [17]. Therefore, it is suggested that overweight or obese individuals may have higher values of iron status indicators, which may reflect an increased risk of cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 99%